Estimating the Effects of Oil Prices on Trade Balance in Saudi Arabia: Bounds Testing to Cointegration Approach - Elfaki, Mansour Ahmed Elmansour; Elsharif, Mohamed Sharif Bashir (International Journal of Energy Economics and Policy, 2025)
The main objective of this study is to examine the effects of oil prices on the trade balance of the Kingdom of Saudi Arabia during the period 1980–2022. In this context, oil prices are analyzed to determine their impact on improving Saudi Arabia’s trade balance in both the short and long term. This is achieved using the bounds testing to cointegration approach and the error correction model (ECM), which both measure short- and long-run equilibrium relationships between variables. The results of this study confirm a statistically significant positive relationship between oil prices and the trade balance in the short and long term. However, these findings confirm the country’s reliance on the oil sector. The most important contribution of this study lies in its focus on the effects of oil prices on Saudi Arabia’s trade balance, as the largest oil producer and net exporter. It also offers policy implications that address the negative effects of fluctuations in international oil prices on the trade balance.